2012
DOI: 10.1124/mol.111.077446
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Novel Class of c-Jun N-terminal Kinase Inhibitors

Abstract: In efforts to identify novel small molecules with antiinflammatory properties, we discovered a unique series of tetracyclic indenoquinoxaline derivatives that inhibited lipopolysaccharide (LPS)-induced nuclear factor-B/activating protein 1 activation. Compound IQ-1 (11H-indeno[1,2-b]quinoxalin-11-one oxime) was found to be a potent, noncytotoxic inhibitor of pro-inflammatory cytokine [interleukin (IL)-1␣, IL-1␤, IL-6, IL-10, tumor necrosis factor (TNF)-␣, interferon-␥, and granulocyte-macrophage colony-stimula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(121 citation statements)
references
References 76 publications
(85 reference statements)
6
100
0
1
Order By: Relevance
“…We also confirmed that IQ-1S inhibited c-Jun phosphorylation in FLSs (Fig. 3C), which confirms our previous observation in human MonoMac-6 cells (Schepetkin et al, 2012). Together, these data suggest that IQ-1S may protect joints in part by decreasing MMP1/MMP3 expression.…”
Section: Inhibition Of Collagen-induced Arthritis By Iq-1ssupporting
confidence: 80%
See 4 more Smart Citations
“…We also confirmed that IQ-1S inhibited c-Jun phosphorylation in FLSs (Fig. 3C), which confirms our previous observation in human MonoMac-6 cells (Schepetkin et al, 2012). Together, these data suggest that IQ-1S may protect joints in part by decreasing MMP1/MMP3 expression.…”
Section: Inhibition Of Collagen-induced Arthritis By Iq-1ssupporting
confidence: 80%
“…We previously reported that the binding affinities (K d ) of IQ-1S toward JNK1, JNK2, and JNK3 were 390, 360, and 87 nM, respectively (Schepetkin et al, 2012). However, a detailed kinase…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations